Battery
By using a specific proportion of fluorodate carbonate and the first sulfur -containing additives in the electrolyte, the optimized SEI membrane is formed to solve the problem of poor volume expansion and high temperature storage performance during the charging and discharge process of silicon -bearing pole batteries. The high temperature performance and cycle stability of the battery have improved significantly.
Patent Information
- Application Number
- CN202411741096.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-01-21
AI Technical Summary
The volume expansion of the silicon negative electrode battery during charging and discharging leads to structural failure and reduced cycle life, and the high-temperature storage and thermal safety performance are worse, especially under high voltage conditions.
Add a specific proportion to the fluorododonal carbonate and the first sulfur -containing additive to the electrolyte to form a dense and uniform solid electrolyte interface (SEI) film to improve the high temperature storage and thermal safety performance of the battery.
By regulating the content ratio and total content of fluorinated ethylene carbonate and the first sulfur-containing additive, the performance of the SEI film on the negative electrode surface is optimized, and the high-temperature performance and cycle stability of the battery are significantly improved.
Smart Images

Figure CN119340498A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a battery. Background Art
[0002] As communication equipment, electric vehicles and other electronic products have higher and higher requirements for battery energy density, traditional graphite negative electrode materials can no longer meet market demand. Silicon negative electrode has a higher theoretical specific capacity (up to 4200mAh / g at high temperature and about 3580mAh / g at room temperature), which is much higher than graphite negative electrode (theoretical specific capacity is 372mAh / g), so it is regarded as one of the key materials for improving the energy density of lithium batteries. However, the silicon negative electrode will undergo significant volume expansion during the charging and discharging process (the expansion rate can reach more than 300%), resulting in problems such as failure of the negative electrode structure and reduced cycle life.
[0003] Fluoroethylene carbonate (FEC), as an important electrolyte additive, can form a solid electrolyte interface (SEI) film with a tight structure and better performance on the surface of the negative electrode, thereby inhibiting the decomposition of the electrolyte, reducing the battery impedance, and improving the battery's specific capacity, cycle stability and cycle life. Therefore, silicon negative electrode batteries often add a certain amount of FEC to the electrolyte. However, when the proportion of FEC in the silicon negative electrode battery system is high, it will cause a series of problems, such as poor performance such as high-temperature storage and thermal safety. Summary of the invention
[0004] The purpose of the present invention is to overcome the above problems existing in the prior art and provide a battery. The electrolyte of the battery of the present invention has good compatibility with the silicon negative electrode, and the electrolyte includes fluoroethylene carbonate and a first sulfur-containing additive with a specific ratio, which can not only form a dense and uniform SEI film on the surface of the negative electrode, but also form a good protective effect on the negative electrode; it can also improve the high temperature storage and thermal safety performance of the battery.
[0005] In related technologies, silicon negative electrodes are often used in conjunction with FEC, but a higher content of FEC will cause problems with high-temperature storage and poor thermal safety performance. And under high voltage conditions (for example, greater than or equal to 4.55V), the above problems will be more serious. This is because: the silicon negative electrode will expand and crack during the battery charge and discharge cycle, so a higher content of FEC is required to continuously repair the SEI film during the battery charge and discharge cycle, thereby reducing the decomposition of the electrolyte and the oxidation of the silicon negative electrode. However, when the FEC content is too high, it will cause the SEI film to be too dense, which will have a negative impact on the Li + Cause loss, on the other hand will make Li +It cannot freely intercalate and deintercalate through the SEI membrane. In addition, at high temperatures, FEC easily decomposes to produce HF and gases (such as CO2), which can cause the internal pressure of the battery to increase, thus causing safety problems; at the same time, HF can corrode battery materials and affect battery performance.
[0006] The inventors of the present invention have found through extensive research that the fluorosulfonamide molecules in the first sulfur-containing additive structure can be adsorbed on the negative electrode sheet and undergo a reduction reaction on the surface of the silicon-based material to generate LiF and sulfur-containing organic matter on the SEI film, which can improve the mechanical strength and stability of the SEI film under high temperature conditions. In addition, the F atoms in the first sulfur-containing additive structure are strongly connected to S, are not easy to decompose and fall off, and have relatively high stability. Therefore, under high temperature conditions, it is not easy to decompose and produce HF and gas. The first sulfur-containing additive can be used to replace part of FEC, which can reduce the content of FEC in the electrolyte, thereby improving the high temperature performance of the battery.
[0007] However, the first sulfur-containing additive cannot completely replace FEC. This is because: the polymer film formed by FEC has good elasticity and can restrain the volume expansion of silicon; while the film formed by the first sulfur-containing additive does not have the elasticity of the polymer film formed by FEC. If the first sulfur-containing additive completely replaces FEC, it will seriously affect the cycle performance of the battery. In addition, the mass content of the first sulfur-containing additive in the electrolyte should not be too high. This is because: when the content of the first sulfur-containing additive is too high, it is easy to cause uneven distribution of lithium ions, hinder the transmission of lithium ions, thereby increasing the internal resistance of the battery, causing the internal temperature of the battery to be too high, and creating safety hazards.
[0008] Therefore, it is necessary to adjust the content ratio of FEC to the first sulfur-containing additive and the total content of the two, so that the degree of coordination between the two can be optimized, so that the SEI film on the surface of the negative electrode has good ionic conductivity, electronic insulation, mechanical strength and elasticity, and effectively inhibits the volume expansion of the silicon-based material while significantly improving the high-temperature performance of the battery, especially improving the high-temperature storage performance and thermal safety performance of the battery. Based on this, the inventors of the present invention provide the following solution:
[0009] The present invention provides a battery, comprising a negative electrode sheet and an electrolyte; the negative electrode sheet comprises a silicon-based material; the electrolyte comprises fluoroethylene carbonate and a first sulfur-containing additive as shown in Formula I; the ratio a of the mass content of fluoroethylene carbonate in the electrolyte to the mass content of the first sulfur-containing additive in the electrolyte is 1-15, and the sum of the mass content of fluoroethylene carbonate in the electrolyte and the mass content of the first sulfur-containing additive in the electrolyte is 4%-30%;
[0010]
[0011] Wherein, R is selected from a nitrogen-containing n-membered ring or selected from n is an integer of 4-6; R1 and R2 each independently include at least one of the following groups which are substituted or unsubstituted by a substituent: an alkyl group, an alkenyl group, an alkynyl group, a cyano group, a phenyl group, a silane group and a sulfone group; and the substituent includes at least one of an unsaturated bond, F and a cyano group.
[0012] Through the above technical solution, the present invention has at least the following advantages compared with the prior art: the battery of the present invention has excellent cycle stability, low temperature performance and high temperature performance under high voltage conditions.
[0013] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 FIG. 1 is a schematic diagram of a negative electrode sheet in an embodiment of the present invention; wherein, Figure 1 (a) is a top view of the negative electrode sheet. Figure 1 (b) is a cross-sectional view along the thickness direction.
[0015] Figure 2 FIG. 4 is a schematic cross-sectional view of a positive electrode sheet along the thickness direction in an example of the present invention. DETAILED DESCRIPTION
[0016] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0017] The present invention provides a battery, which may include a negative electrode sheet and an electrolyte. The negative electrode sheet may include a silicon-based material. The electrolyte may include fluoroethylene carbonate and a first sulfur-containing additive as shown in Formula I,
[0018]
[0019] Wherein, R is selected from a nitrogen-containing n-membered ring or selected from n is an integer of 4-6; R1 and R2 each independently include at least one of the following groups which are substituted or unsubstituted by a substituent: an alkyl group, an alkenyl group, an alkynyl group, a cyano group, a phenyl group, a silane group and a sulfone group; the substituent may include at least one of an unsaturated bond, F and a cyano group.
[0020] In the present invention, the ratio a of the mass content of fluoroethylene carbonate in the electrolyte to the mass content of the first sulfur-containing additive in the electrolyte can be 1-15 (for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 or 15), and the sum of the mass content of fluoroethylene carbonate in the electrolyte and the mass content of the first sulfur-containing additive in the electrolyte can be 4%-30% (for example, 4%, 5%, 10%, 15%, 20%, 25% or 30%).
[0021] In one embodiment, R is selected from R1 and R2 each independently include at least one of the following groups substituted or unsubstituted by the substituent: C1-C6 alkyl, C2-C6 alkenyl, C2-C6 alkynyl, cyano, phenyl, silane and sulfone. The C1-C6 alkyl refers to: the number of carbon atoms in the alkyl is 1-6; similarly, the C2-C6 alkenyl refers to: the number of carbon atoms in the alkenyl is 2-6; the C2-C6 alkynyl refers to: the number of carbon atoms in the alkynyl is 2-6.
[0022] In one embodiment, R is selected from a nitrogen-containing five-membered ring.
[0023] In one embodiment, a is 1.3-13.
[0024] In one embodiment, a is 4-13.
[0025] In one example, the sum of the mass content of fluoroethylene carbonate in the electrolyte and the mass content of the first sulfur-containing additive in the electrolyte is 10%-20%.
[0026] In one example, the sum of the mass content of fluoroethylene carbonate in the electrolyte and the mass content of the first sulfur-containing additive in the electrolyte is 10%-15%.
[0027] In the present invention, the mass content of fluoroethylene carbonate in the electrolyte is 3%-20%, for example, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%.
[0028] In the present invention, the mass content of the first sulfur-containing additive in the electrolyte is 1%-10%, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%.
[0029] In the present invention, the mass content of fluoroethylene carbonate in the electrolyte and the mass content of the first sulfur-containing additive in the electrolyte can be measured by conventional methods in the art, such as gas chromatography (GC).
[0030] In the present invention, the negative electrode sheet may include a negative electrode current collector and a negative electrode active coating located on at least one side of the negative electrode current collector. The negative electrode active coating includes the silicon-based material. The mass content of silicon in the negative electrode active coating may be 2%-40%, for example, 2%, 5%, 10%, 15%, 20%, 25%, 30%, 35% or 40%.
[0031] In one example, the mass content of silicon in the negative electrode active coating is 5%-30%.
[0032] In one example, the mass content of silicon in the negative electrode active coating is 5%-20%.
[0033] The mass content of silicon in the negative electrode active coating has a great influence on the performance of the battery. The more silicon content, the higher the energy density of the battery, but it also faces a greater volume expansion. Therefore, under the premise of specific fluoroethylene carbonate and the first sulfur-containing additive, by regulating the mass content of silicon in the negative electrode active coating, the battery can further take into account both high energy density and cycle stability.
[0034] In the present invention, the first sulfur-containing additive may include
[0035]
[0036] At least one of .
[0037] In one example, the first sulfur-containing additive includes a substance represented by Formula I-1 and / or a substance represented by Formula I-2.
[0038] The inventors of the present invention have found that the protective film formed by the specific first sulfur-containing additive has higher mechanical strength and stability, and has a stronger protective effect on the negative electrode sheet.
[0039] In the present invention, the electrolyte may further include a second sulfur-containing additive. The sum of the mass content of the first sulfur-containing additive in the electrolyte and the mass content of the second sulfur-containing additive in the electrolyte is b≤15%, for example, 15%, 14%, 13%, 12%, 11%, 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2% or 1%.
[0040] In one example, b≤8%.
[0041] Both the first sulfur-containing additive and the second sulfur-containing additive contain sulfur. When the sulfur content in the electrolyte is too high, the overall reducing property of the electrolyte will be too strong, and it is easy to have excessive reduction reaction with the silicon-based material in the later stage of the battery cycle, resulting in the SEI film on the surface of the silicon-based material being unstable or destroyed. As a result, too many by-products are generated, which aggravates the volume expansion of the silicon-based material and consumes a large amount of lithium salt, which ultimately leads to a continuous decline in the battery cycle performance. Therefore, it is necessary to control the total mass content of the first sulfur-containing additive and the second sulfur-containing additive to be less than 15%, so as to improve the cycle stability of the battery in the later stage of the cycle under normal temperature.
[0042] In the present invention, the mass content of the second sulfur-containing additive in the electrolyte can be measured by conventional methods in the art, such as GC.
[0043] In the present invention, the second sulfur-containing additive may include
[0044]
[0045]
[0046] At least one of .
[0047] In one example, the second sulfur-containing additive includes a substance represented by Formula II-1 and / or a substance represented by Formula II-9.
[0048] In one example, the second sulfur-containing additive includes a substance represented by formula II-1 and a substance represented by formula II-9. The substance represented by formula II-1 and the substance represented by formula II-9 can be mixed in any mass ratio, for example, the mass ratio of the substance represented by formula II-1 to the substance represented by formula II-9 is 1:(0.5-2).
[0049] In the present invention, the electrolyte may further include nitrile additives. Nitrile additives can form a chelate with cobalt ions on the surface of the positive electrode, thereby providing certain protection for the positive electrode. At the same time, nitrile additives can form a chelate structure with lithium ions in the electrolyte, improve the solvation capacity of the electrolyte, and contribute to the rapid migration of lithium ions, thereby improving the charge and discharge performance of the battery. And the first sulfur-containing additive can participate in film formation on the surface of the positive electrode, improve the compactness of the CEI (Cathode Electrolyte Interface) film, thereby inhibiting the dissolution of metal ions. Therefore, the first sulfur-containing additive and the nitrile additive can work together to strengthen the protection of the positive electrode, thereby effectively preventing the oxidative decomposition of the electrolyte under high temperature and high voltage conditions, and improving the cycle stability and safety of the battery.
[0050] In the present invention, the ratio c of the mass content of the first sulfur-containing additive in the electrolyte to the mass content of the nitrile additive in the electrolyte can be 0.1-5, for example, 0.1, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5 or 5.
[0051] In one example, c is 0.2-0.7.
[0052] As described above, since the first sulfur-containing additive can improve the compactness of the CEI film, it will have a certain inhibitory effect on the dissolution of metal ions on the surface of the positive electrode sheet; however, this will affect the complexation of the nitrile additive with the cobalt ions on the surface of the positive electrode sheet. When c is too large (for example, greater than 5), the mass content of the first sulfur-containing additive is too much relative to the nitrile additive, and the CEI film formed by the first sulfur-containing additive on the surface of the positive electrode sheet is too dense, so that the nitrile additive has fewer binding sites with the cobalt ions, resulting in: first, the complexation between the nitrile additive and the cobalt ions is less, which is not conducive to improving the protective effect of the protective film on the surface of the positive electrode sheet; second, the nitrile additive that cannot form a protective effect on the positive electrode side will have a destructive effect on the negative electrode. When c is too small (for example, less than 0.1), at this time, the mass content of the first sulfur-containing additive is too small relative to the nitrile additive, and the CEI film formed by the first sulfur-containing additive on the surface of the positive electrode sheet is not dense enough, which is not conducive to the protective effect on the positive electrode sheet. When c is within a specific range, it is beneficial to increase the high temperature of the battery.
[0053] In the present invention, the mass content of the nitrile additive in the electrolyte may be 0.1%-6%, for example, 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5% or 6%.
[0054] In one example, the mass content of the nitrile additive in the electrolyte is 2%-6%.
[0055] In the present invention, the mass content of the nitrile additive in the electrolyte can be measured by conventional methods in the art, such as GC.
[0056] In the present invention, the nitrile additives may include acetonitrile, propionitrile, butyronitrile, succinonitrile, malononitrile, glutaronitrile, adiponitrile, pimelonitrile, suberonitrile, sunflower dinitrile, 1,2-bis(2-cyanoethoxy)ethane, 1,3,6-hexanetrinitrile, 1,3,5-pentanetricarbonitrile, 1,2,3-propanetricarbonitrile, 1,2,6-hexanetrinitrile, 1,2,3-tris(2-cyanoethoxy)propane, 1,2,4-tris(2-cyanoethoxy)ethane, ethoxy) butane, 1,1,1-tris(cyanoethoxymethylene)ethane, 1,1,1-tris(cyanoethoxymethylene)propane, 3-methyl-1,3,5-tris(cyanoethoxy)pentane, 1,2,7-tris(cyanoethoxy)heptane, 1,2,6-tris(cyanoethoxy)hexane, 1,2,5-tris(cyanoethoxy)pentane, ethylene glycol bis(propionitrile), hexafluorocyclotriphosphazene, pentafluoroethoxycyclotriphosphazene, pentafluoro Phenoxy cyclotriphosphazene, 1,4-dicyano-2-butene, p-fluorobenzonitrile, p-methylbenzonitrile, 2-fluoroadiponitrile, 2,2-difluorosuccinonitrile, 1,5-dicyanopentane, 1,6-dicyanohexane, 1,7-dicyanoheptane, 1,8-dicyanooctane, 1,9-dicyanononane, 1,10-dicyanodecane, 1,12-dicyanododecane, 2,2,4,4-tetramethylglutaronitrile, 1,4-dicyanopentane At least one of 2,6-dicyanoheptane, 2,7-dicyanooctane, 2,8-dicyanononane, 1,6-dicyanodecane, tetramethylsuccinonitrile, 2-methylglutaronitrile, 2,4-dimethylglutaronitrile, 3,5-dioxa-heptanenitrile, 1,4-bis(cyanoethoxy)butane, ethylene glycol di(2-cyanoethyl)ether, tricyanobenzene, acrylonitrile, crotononitrile, trans-butenedinitrile, glycerol trinitrile and trans-hexenedinitrile.
[0057] In one example, the nitrile additive includes succinonitrile, adiponitrile and 1,3,6-hexanetrinitrile, wherein succinonitrile, adiponitrile and 1,3,6-hexanetrinitrile can be mixed in any mass ratio, for example, the mass ratio of succinonitrile, adiponitrile and 1,3,6-hexanetrinitrile is 1:(0.5-1.5):(2-3).
[0058] In the present invention, the electrolyte may further include an organic solvent. The organic solvent may include a carbonate solvent and / or a carboxylate solvent. The carbonate solvent may include, for example, ethylene carbonate (EC) and / or at least one of the following solvents substituted or unsubstituted with fluorine: propylene carbonate (PC), dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate. The carboxylate solvent may include, for example, at least one of the following solvents substituted or unsubstituted with fluorine: ethyl acetate, propyl acetate, n-butyl acetate, isobutyl acetate, n-amyl acetate, isoamyl acetate, methyl propionate (PP), ethyl propionate, n-propyl propionate, methyl butyrate, ethyl butyrate, and ethyl butyrate.
[0059] In the present invention, the electrolyte may further include fluoroether substances. The fluoroether substances include, for example, at least one of bis(2,2,2-trifluoroethyl) ether, 2,2,2-trifluoroethyl-1,1,2,2-tetrafluoroethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether, methyl nonafluorobutyl ether, tris(trifluoroethoxy)methane and ethyl nonafluorobutyl ether.
[0060] In one example, the fluoroether substance includes 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.
[0061] In the present invention, the electrolyte may further include a lithium salt. The lithium salt includes, for example, at least one of lithium hexafluorophosphate (LiPF6), lithium difluorophosphate (LiPO2F2), lithium difluorooxalatoborate (LiDFOB), lithium bis(trifluoromethylsulfonyl imide), lithium difluorobis(oxalatophosphate), lithium bis(oxalatoborate), lithium hexafluoroantimonate, lithium hexafluoroarsenate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide, tris(trifluoromethylsulfonyl)methyllithium and lithium tetrafluoroborate.
[0062] In the present invention, the electrolyte may further include an additive, for example, at least one of vinylene carbonate, vinyl carbonate, vinyl sulfate, fluorobenzene, 1,3-difluorobenzene and 1,4-difluorobenzene.
[0063] The inventors of the present invention have found that, under the specific electrolyte system of the present invention, by regulating the structure of the negative electrode sheet, the high temperature stability of the battery (including high temperature storage performance and thermal safety performance) can be further improved. The reason is that by making a recess on the surface of the negative electrode sheet, the negative electrode sheet can have more liquid storage capacity, increase the electrolyte's ability to infiltrate the negative electrode sheet, so that the FEC can penetrate deeper into the negative electrode sheet to reduce the content of FEC on the surface of the negative electrode sheet. Compared with the FEC located on the surface of the negative electrode sheet, the FEC located inside the negative electrode sheet is not easy to generate HF and gas under high temperature conditions, and can also reduce the reaction of FEC with other components in the electrolyte, thereby reducing the acidity of the electrolyte and the amount of gas generated, which helps to maintain the stability of the internal environment of the battery, reduce the generation and accumulation of harmful substances, and is conducive to further improving the high temperature stability of the battery. And by making a recess on the surface of the negative electrode sheet, the direct contact area of the material can be increased, thereby improving the transmission efficiency of lithium ions between the positive and negative electrode sheets.
[0064] In the present invention, at least one side surface of the negative electrode sheet may have a first concave portion, and the depth of the first concave portion may be 3 μm-40 μm, for example, 3 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm or 40 μm.
[0065] In one example, the depth of the first concave portion is 5 μm-30 μm.
[0066] In one example, the depth of the first recess is 10 μm-25 μm.
[0067] In the present invention, the depth of the first concave portion has a conventional meaning in the art, and refers to the vertical distance from the lowest point in the first concave portion to the surface of the negative electrode sheet. The depth of the first concave portion can be measured by conventional methods in the art, for example, by scanning electron microscopy (SEM), selecting at least 10 first concave portions on a cross-sectional image of the negative electrode sheet along the thickness direction, measuring the depth of each first concave portion, and taking an average value. Another example is by a 3D profilometer.
[0068] In the present invention, the sum of the areas of the orthographic projections of the first recess on the surface of the negative electrode sheet may account for 2%-85% of the area of the negative electrode sheet, for example, 2%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or 85%.
[0069] In one example, the sum of the areas of the orthographic projections of the first recessed portions on the surface of the negative electrode sheet accounts for 5% to 70% of the area of the negative electrode sheet.
[0070] In one example, the sum of the areas of the orthographic projections of the first recessed portions on the surface of the negative electrode sheet accounts for 5%-55% of the area of the negative electrode sheet.
[0071] In the present invention, the area ratio of the sum of the areas of the orthogonal projections of the first recesses on the surface of the negative electrode sheet to the area ratio of the negative electrode sheet refers to: the ratio of the sum of the areas of the orthogonal projections of all the first recesses on the surface of one side of the negative electrode sheet to the surface area of the negative electrode sheet on one side. The area ratio of the sum of the areas of the orthogonal projections of the first recesses on the surface of the negative electrode sheet to the area ratio of the negative electrode sheet can be obtained by testing conventional methods in the art, such as by SEM, measurement and calculation.
[0072] In the present invention, the shape of the orthographic projection of the first recess on the surface of the negative electrode sheet is not limited, for example, it can be circular, rectangular, etc., which can achieve good results. The first recess can be a concave hole or a groove, which can also achieve good results.
[0073] In one embodiment, both sides of the negative electrode sheet have the first recessed portion. Figure 1 FIG. 1 is a schematic diagram of a negative electrode sheet in an embodiment of the present invention; wherein, Figure 1 (a) is a top view of the negative electrode sheet. Figure 1 (b) is a cross-sectional view along the thickness direction. It can be seen from the figure that there are a plurality of first recesses 1 on both sides of the negative electrode sheet.
[0074] In one example, the surface of one side of the negative electrode sheet has the first concave portion, and the surface of the other side of the negative electrode sheet has a first convex portion.
[0075] In the present invention, the height of the first protrusion may be 2 μm-40 μm, for example, 2 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm or 40 μm.
[0076] In one example, the height of the first protrusion is 5 μm-30 μm.
[0077] In one example, the height of the first protrusion is 10 μm-25 μm.
[0078] In the present invention, the height of the first convex portion has a conventional meaning in the art, and refers to the vertical distance from the highest point on the first convex portion to the surface of the negative electrode sheet. The height of the first convex portion can be measured by conventional methods in the art, for example, by SEM, selecting at least 10 first convex portions on a cross-sectional mirror image of the negative electrode sheet along the thickness direction, measuring the height of each first convex portion, and taking the average value. Another example is by a 3D profilometer.
[0079] In the present invention, the sum of the areas of the orthographic projections of the first convex portion on the surface of the negative electrode sheet may account for 2%-85% of the area of the negative electrode sheet, for example, 2%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or 85%.
[0080] In one example, the sum of the areas of the orthographic projections of the first protrusions on the surface of the negative electrode sheet accounts for 5%-70% of the area of the negative electrode sheet.
[0081] In one example, the sum of the areas of the orthographic projections of the first protrusions on the surface of the negative electrode sheet accounts for 5%-55% of the area of the negative electrode sheet.
[0082] In the present invention, the area ratio of the sum of the areas of the orthogonal projections of the first convex portions on the surface of the negative electrode sheet to the area ratio of the negative electrode sheet refers to: the ratio of the sum of the areas of the orthogonal projections of all the first convex portions on the surface of one side of the negative electrode sheet to the surface area of the negative electrode sheet on one side. The area ratio of the sum of the areas of the orthogonal projections of the first convex portions on the surface of the negative electrode sheet to the area ratio of the negative electrode sheet can be obtained by testing conventional methods in the art, such as by SEM, measurement and calculation.
[0083] In the present invention, the shape of the orthographic projection of the first protrusion on the surface of the negative electrode sheet is not limited, and can be, for example, circular, rectangular, etc., which can achieve good effects.
[0084] In one example, the position of the first concave portion on the surface of one side of the negative electrode sheet corresponds to the position of the first convex portion on the surface of the other side of the negative electrode sheet.
[0085] The inventor of the present invention has found that under the specific electrolyte system of the present invention, the cycle stability of the battery can be further improved by regulating the structure of the positive electrode sheet. The reason is that by making a recess on the surface of the positive electrode sheet, the positive electrode sheet can have more liquid storage capacity, increase the wetting ability of the electrolyte to the positive electrode sheet, so that the nitrile additives can penetrate more deeply into the inside of the positive electrode sheet, so as to reduce the content of the nitrile additives on the surface of the positive electrode sheet, so that the nitrile additives can be slowly released and effective during the battery charge and discharge cycle. If the content of the nitrile additives is too much in the early stage of the battery cycle, the internal resistance of the battery will be increased, which will have an adverse effect on the electrical performance. By adding a recess on the surface of the positive electrode sheet, it is possible to ensure that the total amount of nitrile additives remains unchanged, reduce the adverse effect of excessive nitrile additives on the internal resistance of the battery in the early stage of the battery cycle, and make the nitrile additives slowly released as the battery cycles, so as to effectively protect the positive electrode sheet and improve the cycle stability of the battery.
[0086] In the present invention, the battery may further include a positive electrode sheet. At least one side surface of the positive electrode sheet may have a second recess. The depth of the second recess may be 3 μm-40 μm, for example, 3 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm or 40 μm.
[0087] In one example, the second recess has a depth of 5 μm-30 μm.
[0088] In one example, the second recess has a depth of 10 μm-25 μm.
[0089] In the present invention, the depth of the second recess has the conventional meaning in the art, and refers to the vertical distance from the lowest point in the second recess to the surface of the positive electrode sheet. The test method for the depth of the second recess is the same as the test method for the depth of the first recess, and will not be repeated here.
[0090] In the present invention, the sum of the areas of the orthographic projections of the second recess on the surface of the positive electrode sheet may account for 2%-85% of the area of the positive electrode sheet, for example, 2%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or 85%.
[0091] In one example, the sum of the areas of the orthographic projections of the second recessed portion on the surface of the positive electrode sheet accounts for 5%-65% of the area of the positive electrode sheet.
[0092] In one example, the sum of the areas of the orthographic projections of the second recessed portion on the surface of the positive electrode sheet accounts for 5%-55% of the area of the positive electrode sheet.
[0093] In the present invention, the ratio of the area of the sum of the orthographic projections of the second recesses on the surface of the positive electrode sheet to the area of the positive electrode sheet refers to: the ratio of the sum of the orthographic projections of all the second recesses on the surface of one side of the positive electrode sheet to the surface area of the positive electrode sheet on one side. The test method for the ratio of the area of the sum of the orthographic projections of the second recesses on the surface of the positive electrode sheet to the area of the positive electrode sheet is the same as the test method for the first recess, and will not be repeated here.
[0094] In the present invention, the shape of the orthographic projection of the second recess on the surface of the positive electrode sheet is not limited, for example, it can be circular, rectangular, etc., which can achieve good results. The second recess can be a concave hole or a groove, which can also achieve good results.
[0095] In one example, both side surfaces of the positive electrode sheet have the second recessed portion.
[0096] In one example, the surface of one side of the positive electrode sheet has the second concave portion, and the surface of the other side of the positive electrode sheet has a second convex portion. Figure 2 The figure shows a schematic cross-sectional view of a positive electrode sheet along the thickness direction in an example of the present invention. It can be seen from the figure that one side surface of the positive electrode sheet has a second concave portion, and the other side surface has a second convex portion.
[0097] In the present invention, the height of the second protrusion may be 3 μm-40 μm, for example, 3 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm or 40 μm.
[0098] In one example, the height of the second protrusion is 5 μm-30 μm.
[0099] In one example, the height of the second protrusion is 10 μm-25 μm.
[0100] In the present invention, the height of the second convex portion has the conventional meaning in the art, and refers to the vertical distance from the highest point on the second convex portion to the surface of the positive electrode sheet. The test method for the height of the second convex portion is the same as that of the first convex portion, and will not be repeated here.
[0101] In the present invention, the sum of the areas of the orthographic projections of the second convex portion on the surface of the positive electrode sheet may account for 2%-85% of the area of the positive electrode sheet, for example, 2%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or 85%.
[0102] In one example, the sum of the areas of the orthographic projections of the second protrusions on the surface of the positive electrode sheet accounts for 5%-65% of the area of the positive electrode sheet.
[0103] In one example, the sum of the areas of the orthographic projections of the second protrusions on the surface of the positive electrode sheet accounts for 5%-55% of the area of the positive electrode sheet.
[0104] In the present invention, the area ratio of the sum of the orthographic projections of the second convex parts on the surface of the positive electrode sheet to the area ratio of the positive electrode sheet refers to: the ratio of the sum of the orthographic projections of all the second convex parts on the surface of one side of the positive electrode sheet to the surface area of the positive electrode sheet on one side. The test method for the area ratio of the sum of the orthographic projections of the second convex parts on the surface of the positive electrode sheet to the area ratio of the positive electrode sheet is the same as that of the first convex part, which will not be repeated here.
[0105] In the present invention, the shape of the orthographic projection of the second convex portion on the surface of the positive electrode sheet is not limited, and can be, for example, circular, rectangular, etc., which can achieve good effects.
[0106] In one example, the position of the second concave portion on the surface of one side of the positive electrode sheet corresponds to the position of the second convex portion on the surface of the other side of the positive electrode sheet.
[0107] In the present invention, the recesses are manufactured on the surface of the positive electrode sheet and / or the negative electrode sheet by conventional methods in the art, such as using an embossing process (i.e., using a special roller to process the electrode sheet so that one side of the electrode sheet has a recess and the other side has a protrusion); or using a laser to manufacture the recesses.
[0108] In the present invention, the positive electrode sheet may include a positive electrode current collector and a positive electrode active coating located on at least one side of the positive electrode current collector. The positive electrode active coating may include a positive electrode active material. The positive electrode active material may include a chemical formula of LiNi x Co y M z A layered lithium composite oxide of O2, wherein 0≤x≤1, 0≤y≤1, 0≤z≤1, and M includes at least one of Mg, Zn, Ga, Ba, Al, Fe, Cr, Sn, V, Mn, Sc, Ti, Nb, Mo and Zr.
[0109] In the present invention, the positive electrode active coating may further include a positive electrode conductive agent and a positive electrode binder. The positive electrode conductive agent may include a conductive agent conventionally used in the art, for example, including at least one of conductive carbon black, conductive graphite, carbon nanotubes (including multi-walled carbon nanotubes and / or single-walled nanotubes) and graphene. The positive electrode binder may include a binder conventionally used in the art, for example, including at least one of polyvinylidene fluoride, styrene-butadiene rubber, polyacrylic acid, polytetrafluoroethylene and polyethylene oxide.
[0110] In the present invention, the silicon-based material may include at least one of elemental silicon, silicon oxygen, silicon carbon and silicon alloy. The silicon oxygen refers to a composite material including elemental silicon and elemental oxygen. The silicon carbon refers to a composite material including elemental silicon and elemental carbon.
[0111] In one example, the silicon-based material includes silicon carbon.
[0112] In the present invention, the sphericity of the silicon-based material can be 0.8-0.98, for example, 0.8, 0.85, 0.9, 0.95 or 0.98. The median particle size Dv50 of the silicon-based material can be 6 μm-12 μm, for example, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm or 12 μm. The specific surface area of the silicon-based material can be 0.5 m 2 / g-10m 2 / g, for example 0.5m 2 / g, 1m 2 / g, 2m 2 / g, 3m 2 / g, 4m 2 / g, 5m 2 / g, 6m 2 / g, 7m 2 / g, 8m 2 / g, 9m 2 / g or 10m 2 / g.
[0113] In one example, the sphericity of the silicon-based material is 0.85-0.95.
[0114] Appropriate sphericity, median particle size Dv50 and specific surface area can optimize the uniformity of the SEI film, thereby improving the stability of the SEI film. When the median particle size Dv50 of the silicon-based material is small, it will lead to an unstable negative electrode structure and cause the volume expansion / contraction of the silicon-based material to be drastic. Too small a sphericity will increase the specific surface area, increase the formation area of the SEI film and the consumption of the electrolyte, which is not conducive to the cycle stability of the battery.
[0115] In the present invention, the sphericity of the silicon-based material can be obtained by testing by conventional methods in the art, such as taking out the negative electrode sheet in the battery, removing the silicon-based material on the negative electrode sheet by a scraper, and directly taking images of the particles by a particle image workstation, and obtaining the particle size and sphericity of the particles by a scale. The median particle size Dv50 of the silicon-based material can be obtained by testing by conventional methods in the art, such as a laser particle size analyzer. The specific surface area of the silicon-based material can be obtained by testing by conventional methods in the art, such as the BET (Brunauer-Emmett-Teller) method.
[0116] In the present invention, the surface of the silicon-based material has pits. The pits can be irregular or regular. The volume of a single pit can be 0.01 μm 3 -10μm 3 , for example 0.01 μm 3 , 0.05μm 3 , 0.1μm 3 , 0.2μm 3 , 0.3μm 3 , 0.4μm 3 , 0.5μm 3 , 0.6μm 3 , 0.7μm 3 , 0.8μm 3 , 0.9μm 3 , 1μm 3 , 2μm 3 , 3μm 3 , 4μm 3 , 5μm 3 , 6μm 3 , 7μm 3 , 8μm 3 , 9μm 3 or 10μm 3 .
[0117] In one example, the volume of a single pit is 0.05 μm 3 -1μm 3 .
[0118] In one example, the volume of a single pit is 0.05 μm 3 -0.55μm 3 .
[0119] In the present invention, the volume of a single pit can be measured by conventional methods in the art, such as measuring and calculating the volumes of at least 10 pits on the surface of the silicon-based material by SEM, and taking the average value.
[0120] The pits on the surface of the silicon-based material can enhance the inhibitory effect of the SEI film formed by the first sulfur-containing additive and FEC on the volume expansion of the silicon-based material, further improving the high-temperature cycle performance of the battery.
[0121] In the present invention, the negative electrode active coating may include a negative electrode active material. The negative electrode active material includes the silicon-based material. The negative electrode active material may also include a carbon-based material, and the carbon-based material includes, for example, at least one of artificial graphite, natural graphite, mesophase carbon microbeads, hard carbon and soft carbon.
[0122] In the present invention, the negative electrode active coating may further include a negative electrode conductive agent and a negative electrode binder. The negative electrode conductive agent may include a conductive agent conventionally used in the art, for example, including at least one of conductive carbon black, conductive graphite, carbon nanotubes (including multi-walled carbon nanotubes and / or single-walled nanotubes) and graphene. The negative electrode binder may include a binder conventionally used in the art, for example, including at least one of polyvinylidene fluoride, styrene-butadiene rubber, polyacrylic acid, polytetrafluoroethylene and polyethylene oxide.
[0123] In the present invention, the upper limit voltage of the battery is 4.55V and above.
[0124] In the present invention, the battery may further include a separator, which may be a conventional one in the art.
[0125] It should be noted that the numerical expressions such as "first" and "second" in the present invention are only used to distinguish different substances or usages, and do not represent the difference in order.
[0126] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.
[0127] In the following examples, unless otherwise specified, all materials used were commercially available of analytical grade.
[0128] The following examples are provided to illustrate the batteries of the present invention.
[0129] Example 1
[0130] Prepare the battery as follows:
[0131] (1) Preparation of electrolyte
[0132] In a glove box (H2O<0.01ppm, O2<0.01ppm, Ar atmosphere), EC, PC and PP were mixed in a mass ratio of 1:1:8 to form an organic solvent; 13% of fluoroethylene carbonate based on the total mass of the electrolyte, 1% of the first sulfur-containing additive represented by formula I-1, 4% of the second sulfur-containing additive (the substance represented by formula II-1 and the substance represented by formula II-9 were mixed in a mass ratio of 2:1), 5% of A nitrile additive (succinonitrile, adiponitrile and 1,3,6-hexanetrinitrile are mixed in a mass ratio of 1:1:1), 10% of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether and 14.5% of LiPF6 are stirred evenly, and after passing the water content and free acid test, an electrolyte is obtained, wherein the sum of the mass contents of the organic solvent, fluoroethylene carbonate, the first sulfur-containing additive, the second sulfur-containing additive, the nitrile additive, the fluoroether substance and the lithium salt is 100%;
[0133] Wherein, a is 13, the sum of the mass contents of fluoroethylene carbonate and the first sulfur-containing additive is 14%, b is 5%, and c is 0.2.
[0134] (2) Preparation of negative electrode sheet
[0135] Artificial graphite, silicon-carbon material (silicon content of 62%, sphericity of 0.9, median particle size Dv50 of 8 μm, specific surface area of 4 m 2 / g, the silicon carbon surface has pits, and the volume of a single pit is 0.188μm 3 ), conductive carbon black, styrene-butadiene rubber and sodium carboxymethyl cellulose are mixed uniformly in a mass ratio of 73:24:2:0.5:0.5, deionized water is added, and the mixture is stirred thoroughly to form a uniform negative electrode slurry; the negative electrode slurry is coated on a copper foil, dried, rolled, cut, and cleaned; a special roller with protrusions is used for processing to obtain a negative electrode sheet having a first concave portion on one surface and a first convex portion on the other surface;
[0136] Among them, the depth of the first concave portion is 14μm, and the sum of the areas of the orthographic projections of the first concave portion on the surface of the negative electrode sheet accounts for 36% of the area of the negative electrode sheet; the height of the first convex portion is 13μm, and the sum of the areas of the orthographic projections of the first convex portion on the surface of the negative electrode sheet accounts for 35% of the area of the negative electrode sheet; the position of the first concave portion on the surface of one side of the negative electrode sheet corresponds one to one with the position of the first convex portion on the surface of the other side of the negative electrode sheet; the mass content of silicon element in the negative electrode active coating is approximately 15%.
[0137] (3) Preparation of positive electrode sheet
[0138] The lithium cobalt oxide, conductive carbon black and polyvinylidene fluoride are mixed evenly in a mass ratio of 97.6:1.35:1.05 in N-methylpyrrolidone (NMP), and stirred evenly to prepare a positive electrode slurry; the positive electrode slurry is evenly coated on the front and back sides of the aluminum foil; the positive electrode slurry is dried, rolled and slit in sequence, and then processed using a special roller with protrusions to obtain a positive electrode sheet having a second concave portion on one side and a second convex portion on the other side;
[0139] Among them, the depth of the second concave portion is 11μm, and the sum of the areas of the orthographic projections of the first concave portions on the surface of the negative electrode sheet accounts for 50% of the area on the negative electrode sheet; the height of the first convex portion is 10μm, and the sum of the areas of the orthographic projections of the first convex portion on the surface of the negative electrode sheet accounts for 49% of the area on the negative electrode sheet; the position of the first concave portion on the surface of one side of the negative electrode sheet corresponds one to one with the position of the first convex portion on the surface of the other side of the negative electrode sheet.
[0140] (4) Preparation of batteries
[0141] The negative electrode sheet prepared in step (2), the positive electrode sheet prepared in step (3) and the separator (polypropylene film with a thickness of 7 μm) are wound into a core according to a predetermined process, and the electrolyte prepared in step (1) is injected. After vacuum sealing, standing, formation, sorting, and secondary sealing, a battery is prepared.
[0142] Example 2
[0143] In a glove box (H2O<0.01ppm, O2<0.01ppm, Ar atmosphere), EC, PC and PP are mixed in a mass ratio of 1:1:8 to form an organic solvent; 12% of fluoroethylene carbonate, 3% of the first sulfur-containing additive shown in formula I-1, 3% of the second sulfur-containing additive (the substance shown in formula II-1 and the substance shown in formula II-9 are mixed in a mass ratio of 1:1), 4.5% of nitrile additives (succinonitrile, adiponitrile and 1,3,6-hexanetrinitrile are mixed in a mass ratio of 1:0.5:2), 10% of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether and 14.5% of LiPF6 are added to the above organic solvent, and the mixture is stirred evenly. After passing the moisture and free acid tests, an electrolyte is obtained;
[0144] Wherein, a is 4, the sum of the mass contents of fluoroethylene carbonate and the first sulfur-containing additive is 15%, b is 6%, and c is 0.67.
[0145] (2) Preparation of negative electrode sheet
[0146] Artificial graphite, silicon-carbon material (silicon content of 62%, sphericity of 0.85, median particle size Dv50 of 8 μm, specific surface area of 4 m 2 / g, the silicon carbon surface has pits, and the volume of a single pit is 0.053μm 3 ), conductive carbon black, styrene-butadiene rubber and sodium carboxymethyl cellulose are mixed uniformly in a mass ratio of 73:24:2:0.5:0.5, deionized water is added, and the mixture is stirred thoroughly to form a uniform negative electrode slurry; the negative electrode slurry is coated on a copper foil, dried, rolled, cut, and cleaned; a special roller with protrusions is used for processing to obtain a negative electrode sheet having a first concave portion on one surface and a first convex portion on the other surface;
[0147] Among them, the depth of the first concave portion is 11μm, and the sum of the areas of the orthographic projections of the first concave portion on the surface of the negative electrode sheet accounts for 52% of the area on the negative electrode sheet; the height of the first convex portion is 10μm, and the sum of the areas of the orthographic projections of the first convex portion on the surface of the negative electrode sheet accounts for 51% of the area on the negative electrode sheet; the position of the first concave portion on the surface of one side of the negative electrode sheet corresponds one to one with the position of the first convex portion on the surface of the other side of the negative electrode sheet.
[0148] (3) Preparation of positive electrode sheet
[0149] Nickel-cobalt-manganese (NCM622) ternary material, conductive carbon black and polyvinylidene fluoride are uniformly mixed in a mass ratio of 97.6:1.35:1.05 in N-methylpyrrolidone (NMP), and stirred to obtain a positive electrode slurry; the positive electrode slurry is uniformly coated on both sides of an aluminum foil; the positive electrode slurry is dried, rolled and slit in sequence, and then processed using a special roller with protrusions to obtain a positive electrode sheet having a second concave portion on one side and a second convex portion on the other side;
[0150] Among them, the depth of the second concave portion is 24μm, and the sum of the areas of the orthographic projections of the first concave portions on the surface of the negative electrode sheet accounts for 16% of the area of the negative electrode sheet; the height of the first convex portion is 22μm, and the sum of the areas of the orthographic projections of the first convex portion on the surface of the negative electrode sheet accounts for 15% of the area of the negative electrode sheet; the position of the first concave portion on the surface of one side of the negative electrode sheet corresponds one to one with the position of the first convex portion on the surface of the other side of the negative electrode sheet.
[0151] (4) Preparation of batteries
[0152] The negative electrode sheet prepared in step (2), the positive electrode sheet prepared in step (3) and the separator (polypropylene film with a thickness of 7 μm) are wound into a core according to a predetermined process, and the electrolyte prepared in step (1) is injected. After vacuum sealing, standing, formation, sorting, and secondary sealing, a battery is prepared.
[0153] Example 3
[0154] In a glove box (H2O<0.01ppm, O2<0.01ppm, Ar atmosphere), EC, PC and PP are mixed in a mass ratio of 1:1:8 to form an organic solvent; 9% of fluoroethylene carbonate based on the total mass of the electrolyte, 2% of the first sulfur-containing additive shown in formula I-2, 5% of the second sulfur-containing additive (the substance shown in formula II-1 and the substance shown in formula II-9 are mixed in a mass ratio of 1:2), 6% of nitrile additives (succinonitrile, adiponitrile and 1,3,6-hexanetrinitrile are mixed in a mass ratio of 1:1.5:3), 10% of 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether and 14.5% of LiPF6 are added to the above organic solvent, and the mixture is stirred evenly. After passing the moisture and free acid tests, an electrolyte is obtained;
[0155] Wherein, a is 4.5, the sum of the mass contents of fluoroethylene carbonate and the first sulfur-containing additive is 11%, b is 7%, and c is 0.33.
[0156] (2) Preparation of negative electrode sheet
[0157] Artificial graphite, silicon-carbon material (silicon content of 62%, sphericity of 0.95, median particle size Dv50 of 8 μm, specific surface area of 4 m 2 / g, the silicon carbon surface has pits, and the volume of a single pit is 0.518μm 3 ), conductive carbon black, styrene-butadiene rubber and sodium carboxymethyl cellulose are mixed uniformly in a mass ratio of 73:24:2:0.5:0.5, deionized water is added, and the mixture is stirred thoroughly to form a uniform negative electrode slurry; the negative electrode slurry is coated on a copper foil, dried, rolled, cut, and cleaned; a special roller with protrusions is used for processing to obtain a negative electrode sheet having a first concave portion on one surface and a first convex portion on the other surface;
[0158] Among them, the depth of the first concave portion is 23μm, and the sum of the areas of the orthographic projections of the first concave portion on the surface of the negative electrode sheet accounts for 13% of the area of the negative electrode sheet; the height of the first convex portion is 21μm, and the sum of the areas of the orthographic projections of the first convex portion on the surface of the negative electrode sheet accounts for 14% of the area of the negative electrode sheet; the position of the first concave portion on the surface of one side of the negative electrode sheet corresponds one to one with the position of the first convex portion on the surface of the other side of the negative electrode sheet.
[0159] (3) Preparation of positive electrode sheet
[0160] Nickel-cobalt-manganese (NCM613) ternary material, conductive carbon black and polyvinylidene fluoride are uniformly mixed in a mass ratio of 97.6:1.35:1.05 in N-methylpyrrolidone (NMP), and stirred to obtain a positive electrode slurry; the positive electrode slurry is uniformly coated on both sides of an aluminum foil; the positive electrode slurry is dried, rolled and slit in sequence, and then processed using a special roller with protrusions to obtain a positive electrode sheet having a second concave portion on one side and a second convex portion on the other side;
[0161] Among them, the depth of the second concave portion is 16μm, and the sum of the areas of the orthographic projections of the first concave portions on the surface of the negative electrode sheet accounts for 34% of the area on the negative electrode sheet; the height of the first convex portion is 15μm, and the sum of the areas of the orthographic projections of the first convex portion on the surface of the negative electrode sheet accounts for 32% of the area on the negative electrode sheet; the position of the first concave portion on the surface of one side of the negative electrode sheet corresponds one to one with the position of the first convex portion on the surface of the other side of the negative electrode sheet.
[0162] (4) Preparation of batteries
[0163] The negative electrode sheet prepared in step (2), the positive electrode sheet prepared in step (3) and the separator (polypropylene film with a thickness of 7 μm) are wound into a core according to a predetermined process, and the electrolyte prepared in step (1) is injected. After vacuum sealing, standing, formation, sorting, and secondary sealing, a battery is prepared.
[0164] Example 4
[0165] Used to verify the impact of changes in "the ratio a of the mass content of fluoroethylene carbonate to the first sulfur-containing additive in the electrolyte".
[0166] The method is carried out with reference to Example 3, except that a is regulated by changing the content of the first sulfur-containing substance in the electrolyte, as follows:
[0167] The mass content of the first sulfur-containing additive is 3%;
[0168] Among them, a is 3.
[0169] Example 5 Group
[0170] This group of examples is used to verify the influence of the change of "the sum of the mass contents of fluoroethylene carbonate and the first sulfur-containing additive".
[0171] This group of examples is carried out with reference to Example 1, except that the sum of the mass contents of the fluoroethylene carbonate and the first sulfur-containing additive is regulated by changing the mass content of the two, as follows:
[0172] Example 5a, the mass content of fluoroethylene carbonate is 18%, the mass content of the first sulfur-containing additive is 10%; the sum of the mass contents of fluoroethylene carbonate and the first sulfur-containing additive is 28%;
[0173] In Example 5b, the mass content of fluoroethylene carbonate is 3%, the mass content of the first sulfur-containing additive is 1%, and the sum of the mass contents of fluoroethylene carbonate and the first sulfur-containing additive is 4%.
[0174] Example 6 Group
[0175] This group of examples is used to verify the impact of changes in the "first sulfur-containing additive".
[0176] This group of examples is carried out with reference to Example 1, except that the first sulfur-containing additive is changed, as follows:
[0177] Example 6a, replacing the substance represented by formula I-1 with the substance represented by formula I-8 of the same mass;
[0178] Example 6b, replacing the substance represented by formula I-1 with the same mass of the substance represented by formula I-17.
[0179] Example 7 Group
[0180] This group of examples is used to verify the impact of the change of the "second sulfur-containing additive".
[0181] This group of examples is carried out with reference to Example 1, except that the second sulfur-containing additive is changed, as follows:
[0182] Example 7a, the second sulfur-containing additive is replaced with the substance represented by formula II-3 of the same mass;
[0183] Example 7b, the second sulfur-containing additive is replaced by the substance represented by formula II-6 of the same mass.
[0184] Example 8
[0185] Used to verify the impact of the change in "the sum of the mass contents of the first sulfur-containing additive and the second sulfur-containing additive in the electrolyte b".
[0186] The method is carried out in accordance with Example 1, except that b is regulated by changing the mass content of the second sulfur-containing additive in the electrolyte, specifically:
[0187] The mass content of the second sulfur-containing additive in the electrolyte is 9%; b is 10%.
[0188] Example 9
[0189] Used to verify the impact of "whether nitrile additives are added".
[0190] The process is carried out in accordance with Example 1, except that no nitrile additive is added to the electrolyte.
[0191] Example 10 Group
[0192] This group of examples is used to verify the influence of the change of "the ratio c of the mass content of the first sulfur-containing additive in the electrolyte to the mass content of the nitrile additive in the electrolyte".
[0193] This group of examples is carried out with reference to Example 1, except that c is regulated by changing the mass content of the first sulfur-containing additive in the electrolyte and / or the mass content of the nitrile additive in the electrolyte, as follows:
[0194] Example 10a, the mass content of the nitrile additive in the electrolyte is 6%, and c is 0.17;
[0195] In Example 10b, the mass content of the first sulfur-containing additive in the electrolyte is 10%, the mass content of the nitrile additive in the electrolyte is 2%, and c is 0.5.
[0196] Example 11 Group
[0197] This group of examples is used to verify the impact of changes in the "mass content of silicon in the negative electrode active coating".
[0198] This group of examples is carried out with reference to Example 1, except that the mass content of silicon in the negative electrode active coating is regulated by adjusting the content of each component in the negative electrode slurry, as follows:
[0199] In Example 11a, the mass ratio of artificial graphite, silicon-carbon material, conductive carbon black, styrene-butadiene rubber and sodium carboxymethyl cellulose is 89:8:2:0.5:0.5, and the mass content of silicon in the negative electrode active coating is about 5%;
[0200] In Example 11b, the mass ratio of artificial graphite, silicon-carbon material, conductive carbon black, styrene-butadiene rubber and sodium carboxymethyl cellulose is 65:32:2:0.5:0.5, and the mass content of silicon in the negative electrode active coating is about 20%;
[0201] In Example 11c, the mass ratio of artificial graphite, silicon-carbon material, conductive carbon black, styrene-butadiene rubber and sodium carboxymethyl cellulose is 94:3:2:0.5:0.5, and the mass content of silicon in the negative electrode active coating is about 2%;
[0202] In Example 11d, the mass ratio of artificial graphite, silicon-carbon material, conductive carbon black, styrene-butadiene rubber and sodium carboxymethyl cellulose is 49:48:2:0.5:0.5, and the mass content of silicon element in the negative electrode active coating is about 30%.
[0203] Example 12 Group
[0204] This group of embodiments is used to verify the effects of changes in “the first concave portion and / or the first convex portion on the surface of the negative electrode sheet and the second concave portion and / or the second convex portion on the surface of the positive electrode sheet”.
[0205] This group of examples is carried out with reference to Example 1, as follows:
[0206] Embodiment 12a, the positive electrode sheet and the negative electrode sheet are processed without using a protruding special roller (that is, the surface of the negative electrode sheet does not have the first concave portion and the first convex portion, and the surface of the positive electrode sheet does not have the second concave portion and the second convex portion);
[0207] Embodiment 12b, the positive electrode sheet is processed without using a protruding special roller (that is, the surface of the positive electrode sheet has no second concave portion and second convex portion);
[0208] In Example 12c, the negative electrode sheet is processed without using a special roller with projections (ie, the surface of the negative electrode sheet does not have the first concave portion and the first convex portion).
[0209] Example 13
[0210] This is used to verify the impact of the change in the “manufacturing process of the first recess”.
[0211] The method is carried out in accordance with Example 1, except that a laser is used to make recesses (grooves) on both sides of the negative electrode sheet, as follows:
[0212] In step (2) of preparing the negative electrode sheet, after cleaning, a laser is used to make grooves (first recesses) on both sides of the negative electrode sheet, wherein the depth of the first recess is 14 μm, and the sum of the areas of the positive projections of the first recess on the surface of the negative electrode sheet accounts for 35% of the area of the negative electrode sheet.
[0213] Example 14 Group
[0214] This group of embodiments is used to verify the influence of changes in “the dimensions of the first concave portion, the first convex portion, the second concave portion, and the second convex portion”.
[0215] This group of examples is carried out with reference to Example 1, except that the sizes of the first concave portion, the first convex portion, the second concave portion and the second convex portion are adjusted by changing the size of the convexities on the special roller containing the convexities, as follows:
[0216] In Example 14a, the depth of the first concave portion is 3 μm, and the sum of the areas of the orthographic projections of the first concave portion on the surface of the negative electrode sheet accounts for 70% of the area of the negative electrode sheet; the height of the first convex portion is 2 μm, and the sum of the areas of the orthographic projections of the first convex portion on the surface of the negative electrode sheet accounts for 68% of the area of the negative electrode sheet; the depth of the second concave portion is 5 μm, and the sum of the areas of the orthographic projections of the first concave portion on the surface of the negative electrode sheet accounts for 65% of the area of the negative electrode sheet; the height of the first convex portion is 4 μm, and the sum of the areas of the orthographic projections of the first convex portion on the surface of the negative electrode sheet accounts for 63% of the area of the negative electrode sheet;
[0217] In Example 14b, the depth of the first concave portion is 40 μm, and the sum of the areas of the orthographic projections of the first concave portions on the surface of the negative electrode sheet accounts for 10% of the area of the negative electrode sheet; the height of the first convex portion is 38 μm, and the sum of the areas of the orthographic projections of the first convex portions on the surface of the negative electrode sheet accounts for 9% of the area of the negative electrode sheet; the depth of the second concave portion is 38 μm, and the sum of the areas of the orthographic projections of the first concave portions on the surface of the negative electrode sheet accounts for 12% of the area of the negative electrode sheet; the height of the first convex portion is 35 μm, and the sum of the areas of the orthographic projections of the first convex portions on the surface of the negative electrode sheet accounts for 11% of the area of the negative electrode sheet.
[0218] Comparative Example 1
[0219] The process is carried out in accordance with Example 1, except that the first sulfur-containing additive is not added to the electrolyte.
[0220] Comparative Example 2
[0221] The process is carried out in accordance with Example 1, except that fluoroethylene carbonate is not added to the electrolyte, and the mass content of the first additive is adjusted to 14%.
[0222] Comparative Example 3
[0223] Refer to Example 1, except that the mass contents of fluoroethylene carbonate and the first additive in the electrolyte are changed. Specifically, the mass content of fluoroethylene carbonate is 20%, the mass content of the first additive is 1%, a is 20, and the sum of the mass contents of fluoroethylene carbonate and the first sulfur-containing additive is 21%.
[0224] Comparative Example 4
[0225] Refer to Example 1, except that the mass contents of fluoroethylene carbonate and the first additive in the electrolyte are changed. Specifically, the mass content of fluoroethylene carbonate is 20%, the mass content of the first additive is 15%, a is 1.33, and the sum of the mass contents of fluoroethylene carbonate and the first sulfur-containing additive is 35%.
[0226] Test Case
[0227] (1) 25℃ cycle test
[0228] The batteries prepared in the examples and comparative examples were subjected to a 25°C cycle test. The specific test method is as follows:
[0229] At 25°C, let the battery stand for 10 min; discharge at 1C to a lower limit voltage of 3.0 V, and let stand for 10 min; charge at 1C to an upper limit voltage of 4.55 V, with a cutoff current of 0.025C, and let stand for 10 min; discharge at a rate of 1.2C to a cutoff voltage of 3.0 V, and let stand for 10 min; cycle for 600 T, and record the capacity Q1 after 600 T of cycling and the initial discharge capacity Q0. The 25°C cycle capacity retention rate (%) = Q1 / Q0 × 100%. The results are recorded in Table 1.
[0230] (2) 0℃ cycle test
[0231] The batteries prepared in the examples and comparative examples were subjected to a 0°C cycle test. The specific test method is as follows:
[0232] In a 0℃ environment, let the battery stand for 10 minutes; discharge at 1C to a lower limit voltage of 3.0V, and let it stand for 10 minutes; charge at 1C to an upper limit voltage of 4.55V, with a cutoff current of 0.025C, and let it stand for 10 minutes; discharge at a rate of 1.2C to a cutoff voltage of 3.0V, and let it stand for 10 minutes; cycle for 600T, and record the capacity Q2 after cycling at 0℃ for 600T and the initial discharge capacity Q0, then the 0℃ cycle capacity retention rate (%) = Q2 / Q0×100%, and the results are recorded in Table 1.
[0233] (3) 45℃ cycle test
[0234] The batteries prepared in the examples and comparative examples were subjected to a 45°C cycle test. The specific test method is as follows:
[0235] At 45°C, let the battery stand for 10 min; discharge at 1C to a lower limit voltage of 3.0V, and let stand for 10 min; charge at 1C to an upper limit voltage of 4.55V, with a cutoff current of 0.025C, and let stand for 10 min; discharge at a rate of 1.2C to a cutoff voltage of 3.0V, and let stand for 10 min; cycle for 600T, and record the capacity Q3 after cycling at 45°C for 600T and the initial discharge capacity Q0. The 45°C cycle capacity retention rate (%) = Q3 / Q0×100%. The results are recorded in Table 1.
[0236] (4) Furnace temperature test
[0237] The batteries prepared in the examples and comparative examples were subjected to furnace temperature tests. The specific test methods are as follows:
[0238] Under 25°C environment, the battery is discharged at 0.2C to a lower limit voltage of 3.0V, and allowed to stand for 10 minutes; it is charged at 1C to an upper limit voltage of 4.55V, with a cut-off current of 0.05C, at which time the battery is fully charged; the voltage, internal resistance, thickness and weight of the fully charged battery are tested; then the fully charged battery is placed in an oven, and the temperature is increased at a heating rate of 5°C / min. When the temperature in the box reaches 132°C, the temperature is kept constant for 60 minutes, and the battery status is recorded. In the test phase, 10 batteries are tested for each embodiment and comparative example, and the pass rate of each embodiment and comparative example is recorded. If all 10 batteries do not catch fire or explode, 10 / 10 is recorded; if 8 batteries out of 10 batteries do not catch fire or explode, 8 / 10 is recorded. The results are recorded in Table 1.
[0239] (5) High temperature storage
[0240] The batteries prepared in the examples and comparative examples were stored at high temperature, and the specific test method was as follows:
[0241] At 25℃±3℃, discharge at 0.5C to the lower limit voltage and let stand for 10min. Place the battery in a 25℃ constant temperature box and fully charge it at 0.5C constant current with a cut-off current of 0.02C. After full charge, test the initial thickness t0 of the battery body. Store the battery in an 85℃ environment. After 6h of storage, test the thickness t1 of the battery body. The thickness expansion rate of the battery is (t1-t0) / t0×100%. Record the results in Table 1.
[0242] Table 1
[0243]
[0244]
[0245] As can be seen from Table 1, the battery of the present invention has excellent cycle stability, low temperature performance and high temperature performance under high voltage conditions compared with the comparative example. The difference between Example 11 and Example 1 is the mass content of silicon in the negative electrode active coating. Therefore, among the five examples of Example 1 and Example 11, the order of the energy density of the battery from large to small is Example 11d> Example 11b> Example 1> Example 11a> Example 11c.
[0246] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A battery, characterized in that: Including negative electrode sheet and electrolyte; The negative electrode sheet comprises a silicon-based material; The electrolyte comprises fluoroethylene carbonate and a first sulfur-containing additive as shown in formula I; the ratio a of the mass content of fluoroethylene carbonate in the electrolyte to the mass content of the first sulfur-containing additive in the electrolyte is 1-15, and the sum of the mass content of fluoroethylene carbonate in the electrolyte and the mass content of the first sulfur-containing additive in the electrolyte is 4%-30%; Wherein, R is selected from a nitrogen-containing n-membered ring or selected from n is an integer of 4-6; R1 and R2 each independently include at least one of the following groups which are substituted or unsubstituted by a substituent: an alkyl group, an alkenyl group, an alkynyl group, a cyano group, a phenyl group, a silane group and a sulfone group; and the substituent includes at least one of an unsaturated bond, F and a cyano group.
2. The battery according to claim 1, wherein a is 1.3-13; preferably 4-13; And / or, the sum of the mass content of fluoroethylene carbonate in the electrolyte and the mass content of the first sulfur-containing additive in the electrolyte is 10%-20%; preferably 10%-15%; And / or, the mass content of fluoroethylene carbonate in the electrolyte is 3%-20%; And / or, the mass content of the first sulfur-containing additive in the electrolyte is 1%-10%; And / or, the negative electrode sheet comprises a negative electrode current collector and a negative electrode active coating located on at least one side of the negative electrode current collector, the negative electrode active coating comprises the silicon-based material; the mass content of silicon element in the negative electrode active coating is 2%-40%, preferably 5%-20%.
3. The battery according to claim 1 or 2, wherein: The first sulfur-containing additive comprises At least one of; Preferably, the first sulfur-containing additive comprises and / or 4. The battery according to claim 1 or 2, wherein The electrolyte further includes a second sulfur-containing additive, wherein the sum of the mass content of the first sulfur-containing additive in the electrolyte and the mass content of the second sulfur-containing additive in the electrolyte is b≤15%; preferably, b≤8%; Preferably, the second sulfur-containing additive comprises At least one of .
5. The battery according to claim 1 or 2, wherein The electrolyte also includes a nitrile additive; Preferably, the ratio c of the mass content of the first sulfur-containing additive in the electrolyte to the mass content of the nitrile additive in the electrolyte is 0.1-5; more preferably 0.2-0.7; Preferably, the mass content of the nitrile additive in the electrolyte is 0.1%-6%; Preferably, the nitrile additives include acetonitrile, propionitrile, butyronitrile, succinonitrile, malononitrile, glutaronitrile, adiponitrile, pimelonitrile, suberonitrile, sunflower dinitrile, 1,2-bis(2-cyanoethoxy)ethane, 1,3,6-hexanetrinitrile, 1,3,5-pentanetricarbonitrile, 1,2,3-propanetricarbonitrile, 1,2,6-hexanetrinitrile, 1,2,3-tris(2-cyanoethoxy)propane, 1,2,4-tris(2-cyanoethoxy)ethane ) butane, 1,1,1-tris(cyanoethoxymethylene)ethane, 1,1,1-tris(cyanoethoxymethylene)propane, 3-methyl-1,3,5-tris(cyanoethoxy)pentane, 1,2,7-tris(cyanoethoxy)heptane, 1,2,6-tris(cyanoethoxy)hexane, 1,2,5-tris(cyanoethoxy)pentane, ethylene glycol bis(propionitrile), hexafluorocyclotriphosphazene, pentafluoroethoxycyclotriphosphazene, pentafluorophenoxy cyclotriphosphazene, 1,4-dicyano-2-butene, p-fluorobenzonitrile, p-methylbenzonitrile, 2-fluoroadiponitrile, 2,2-difluorosuccinonitrile, 1,5-dicyanopentane, 1,6-dicyanohexane, 1,7-dicyanoheptane, 1,8-dicyanooctane, 1,9-dicyanononane, 1,10-dicyanodecane, 1,12-dicyanododecane, 2,2,4,4-tetramethylglutaronitrile, 1,4-dicyanopentane , 2,6-dicyanoheptane, 2,7-dicyanooctane, 2,8-dicyanononane, 1,6-dicyanodecane, tetramethylsuccinonitrile, 2-methylglutaronitrile, 2,4-dimethylglutaronitrile, 3,5-dioxa-heptanenitrile, 1,4-bis(cyanoethoxy)butane, ethylene glycol di(2-cyanoethyl) ether, tricyanobenzene, acrylonitrile, crotononitrile, trans-butenedinitrile, glycerol trinitrile and trans-hexenedinitrile.
6. The battery according to claim 1 or 2, wherein: The negative electrode sheet has a first concave portion on at least one side surface; Preferably, the depth of the first concave portion is 3 μm-40 μm; more preferably 5 μm-30 μm; Preferably, the sum of the areas of the orthographic projections of the first recesses on the surface of the negative electrode sheet accounts for 2%-85% of the area of the negative electrode sheet; more preferably, 5%-55%.
7. The battery according to claim 6, wherein The negative electrode sheet has the first concave portion on one side surface and the negative electrode sheet has the first convex portion on the other side surface; Preferably, the height of the first convex portion is 2 μm-40 μm; more preferably 5 μm-30 μm; Preferably, the sum of the areas of the orthographic projections of the first protrusions on the surface of the negative electrode sheet accounts for 2%-85% of the area of the negative electrode sheet; more preferably, 5%-55%.
8. The battery according to claim 1 or 2, wherein: The battery further comprises a positive electrode sheet; at least one side surface of the positive electrode sheet has a second recess; Preferably, the depth of the second concave portion is 3 μm-40 μm; more preferably 5 μm-30 μm; Preferably, the sum of the areas of the orthographic projections of the second recesses on the surface of the positive electrode sheet accounts for 2%-85% of the area of the positive electrode sheet; more preferably, 5%-55%.
9. The battery according to claim 8, wherein The surface of one side of the positive electrode sheet has the second concave portion, and the surface of the other side of the positive electrode sheet has a second convex portion; Preferably, the height of the second protrusion is 3 μm-40 μm; more preferably 5 μm-30 μm; Preferably, the sum of the areas of the orthographic projections of the second convex portions on the surface of the positive electrode sheet accounts for 2%-85% of the area of the positive electrode sheet; more preferably, 5%-55%.
10. The battery according to claim 1 or 2, wherein The silicon-based material satisfies at least one of the following conditions: (a) The silicon-based material includes at least one of elemental silicon, silicon oxygen, silicon carbon and silicon alloy; preferably, the silicon-based material includes the silicon carbon; (b) the sphericity of the silicon-based material is 0.8-0.98; preferably 0.85-0.95; (c) the median particle size Dv50 of the silicon-based material is 6 μm-12 μm; (d) The silicon-based material has pits on its surface, and the volume of a single pit is 0.01 μm 3 -10μm 3 .
Citation Information
Patent Citations
Electrolyte for lithium-ion battery made of ternary cathode materials and lithium-ion battery made of ternary cathode materials
CN105355970A
Lithium ion secondary battery and electrolyte thereof
CN105470571A
Lithium ion battery and electronic device
CN113410511A
High-voltage electrolyte for lithium battery
CN114142088A
Battery with excellent rate capability and high-temperature storage performance
CN118336076A